2022
DOI: 10.3389/fmolb.2021.772788
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Technology in Gene-Editing-Based Detection and Treatment of SARS-CoV-2

Abstract: Outbreak and rapid spread of coronavirus disease (COVID-19) caused by coronavirus acute respiratory syndrome (SARS-CoV-2) caused severe acute respiratory syndrome (SARS-CoV-2) that started in Wuhan, and has become a global problem because of the high rate of human-to-human transmission and severe respiratory infections. Because of high prevalence of SARS-CoV-2, which threatens many people worldwide, rapid diagnosis and simple treatment are needed. Genome editing is a nucleic acid-based approach to altering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 117 publications
(159 reference statements)
0
6
0
Order By: Relevance
“…In recent years, CRISPR (clustered regularly interspaced short palindromic repeats) has been successfully implemented in various applications including the editing of epigenetic factors [ 190 , 191 ] and as a potential option to address heart disease [ 192 ]. Based on the success of CRISPR, it is not surprising that CRISPR has been used to detect SARS-CoV-2 [ 193 , 194 ] and the advantages of CRISPR in various aspects of COVID-19 treatment are being considered [ 195 , 196 ]. As CRISPR is already established in the editing of epigenetic factors and cardiac research, it is only a matter of time before CRISPR is developed as a significant tool against COVID-19-related cardiac and epigenetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, CRISPR (clustered regularly interspaced short palindromic repeats) has been successfully implemented in various applications including the editing of epigenetic factors [ 190 , 191 ] and as a potential option to address heart disease [ 192 ]. Based on the success of CRISPR, it is not surprising that CRISPR has been used to detect SARS-CoV-2 [ 193 , 194 ] and the advantages of CRISPR in various aspects of COVID-19 treatment are being considered [ 195 , 196 ]. As CRISPR is already established in the editing of epigenetic factors and cardiac research, it is only a matter of time before CRISPR is developed as a significant tool against COVID-19-related cardiac and epigenetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, we must bear in mind that the CRISPR technology has its own limitations too since it is pretty much new technology that is still being worked on to understand more of it. The advancement in the technological world has made almost all of these methods achievable within 24 h or even less [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Methods Of Detectionmentioning
confidence: 99%
“… 57 It was reported that depending on the assay technique, CRISPR‐COVID assay costs less than $3.50 for a single reaction. 58 In the near future, CRISPR‐based assays have the potential to become less complicated, more reliable, faster, and more affordable. 59 The detection time is 2–8 h for ELISA.…”
Section: Diagnostic Tests For Covid‐19 Detectionmentioning
confidence: 99%
“…SHERLOCK for SARS‐CoV‐2 detection has demonstrated 93.1% sensitivity and is significantly faster than qRT‐PCR 57 . It was reported that depending on the assay technique, CRISPR‐COVID assay costs less than $3.50 for a single reaction 58 . In the near future, CRISPR‐based assays have the potential to become less complicated, more reliable, faster, and more affordable 59 .…”
Section: Diagnostic Tests For Covid‐19 Detectionmentioning
confidence: 99%